Toxic Prion: Translation of a Genome's gene with a toxic change (British Journal of Multidisciplinary and Advanced Studies, 2022)
Toxic prion is an abnormal form of a normally harmless protein found in the brain that is responsible for a variety of fatal neurodegenerative diseases of animals including humans. These neurodegenerative diseases are called transmissible spongiform encephalopathies. The key objective of this study is to give a spectacular proof of Nature’s Controlled Experiment for the fact that Genome’s designed/coded directives are effected by its transcripts [7] & proteins serving as implementing engineers in synthesizing its individuals in each species of all genomic-things whereas its usable chemical energy-containing nutritive substances including minerals are used as raw materials in its aerobic or anaerobic compatible environment. The micrographs, Figures, videos were designed be the targets of the study and impartive results in aimful approach of the investigator; and, that was why it had been entitled as Methodology & Results. Genome is not only the true automatic molecular machine capable of synthesizing genomic-things, it is also a supersensitive molecule where symptoms, syndromes, epigenetic modifications, immunological defensive reactions, and the capability of toxic prion proteins (PrP 27-30) to induce conversion of normal prion proteins (PrP 33-35) into toxic prion proteins to cause fatal neurodegenerative diseases are evidences for the fact that the Genome is an unbelievably supersensitive automatic molecular machine!!!! Epigenetics is actually the study of supersensitivity of the Genome by attaching epigenetic groups or chemicals to Genome that are not structural parts of the Genome. When toxicity of prion is caused by change, modification, or mutation in one’s own Genome, it is called autotoxic prion and when it is transmitted from other individuals, it is referred to as acquired toxic prion.